Sex chromosome mosaicism (60, XX/61, XXX) in an infertile HF heifer - PATEL, RAJESH KUMAR (The Indian Journal of Animal Reproduction, 2023)
A blood sample was collected from a 4-year old HF heifer because of repeat breeding problem, for cytogenetic investigation.The female had normal external and internal genitals. Chromosome slides were prepared using short term lymphocyte culture. Sexchromosomes mosaicism was ietected as 4% cells were found with abnormal number of sex chromosomes (61,XXX) ~cause of anadditional X chromosome, which could be possible reason for infertility in HF heifer.
Keywords: Sex chromosome; mosaicism; infertility